Alternative Mating Tactics in Socially Monogamous Prairie Voles, Microtus ochrogaster - Shuster, Stephen M.; Willen, Regina M.; Keane, Brian; Solomon, Nancy G. (Frontiers in Ecology and Evolution, 2019)
ABSTRACT: Alternative mating tactics appear to evolve when sexual selection is strong. Because such conditions are usually observed in species with polygynous or polyandrous mating systems, alternative mating tactics in monogamous mating systems are seldom documented and are poorly understood. In prairie voles, Microtus ochrogaster, a species widely known for forming monogamous pair-bonds, the expression of territoriality within each sex is dimorphic, and includes non-territorial “wanderers” as well as territorial “residents.” To explore the variance in fitness, measured in offspring numbers, among breeding individuals expressing these alternative mating tactics, we compiled parentage data over three years for male and female prairie voles from natural populations in Indiana and Kansas, USA. We found that: (1) the average fitnesses of males and females within each population were identical when adjusted by the sex ratio; (2) the variance in fitness in male and female prairie voles was comparable to that of many highly polygynous species; (3) The average fitnesses of male tactics, and of female tactics, were equivalent within and among years within each location; (4) consistent with negative frequency-dependent selection acting on mating phenotypes, the between-tactic variance in fitness for male and female mating tactics decreased with increasing study duration; (5) consistent with negative assortative mating, resident males and wanderer females produced offspring primarily in monogamous partnerships, whereas wanderer males and resident females produced offspring primarily in polygamous partnerships. Our results show that the conditions necessary for the persistence of alternative mating tactics are indistinguishable from those for phenotypically less flexible alternative mating strategies, and that alternative mating tactics can evolve in both sexes in monogamous species when fitness variance within each sex is large.